2022
DOI: 10.1097/mjt.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia in Patients With Clozapine-Treated Schizophrenia: An Effect of Clozapine or a Consequence of SARS-CoV-2 Infection? A Systematic Review

Abstract: Background: Clozapine is the only approved antipsychotic for treatment-resistant schizophrenia. Despite its therapeutic benefits, it is still widely underused, mainly because of its potential to cause agranulocytosis and neutropenia. Prescribing clozapine in COVID-19-positive patients became more challenging because of this potential side effect. This article is a review of literature on the risk of neutropenia associated with clozapine treatment in patients with COVID-19. Areas of Uncertainty:In clozapine-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The same review found that SARS-CoV-2 infected and clozapine-treated patients show a temporary reduction in neutrophils' count; however, vaccination studies did not indicate severe adverse effects. The authors support the previously suggested 9,83 interference of COVID-19 in clozapine metabolism. 91…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The same review found that SARS-CoV-2 infected and clozapine-treated patients show a temporary reduction in neutrophils' count; however, vaccination studies did not indicate severe adverse effects. The authors support the previously suggested 9,83 interference of COVID-19 in clozapine metabolism. 91…”
Section: Discussionsupporting
confidence: 88%
“…Data suggested that TRS patients on clozapine treatment are at no greater risk of developing neutropenia or agranulocytosis if contracting COVID-19 than the noninfected population and that only a mild, transient drop in ANC is to be expected. 9,83…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3130 and 2280 tonnes in 2016, respectively. Consumption is forecast to rise to 7830 tonnes in total by 2023 …”
Section: Introductionmentioning
confidence: 99%
“…After liquid/solid separation, the hydrate is then thermally treated at 150–190 °C to yield the anhydrous form. , This process is considered to be the conventional technology and has been applied by manufacturers worldwide (Jungbunzlauer, Global Calcium, Ningxiang Xinyang Chemical, etc.) to produce magnesium citrate products. ,,, Lab-scale studies designed to prepare magnesium citrate from magnesium-bearing ores such as magnesite (MgCO 3 ) and dolomite (CaCO 3 ·MgCO 3 ) have been described as an alternative. , The process involves acid-citric leaching to yield magnesium citrate solutions, followed by precipitation/crystallization to form magnesium citrate hydrates with subsequent conventional drying. Magnesium citrates have also been synthesized via spray drying of leach solutions .…”
Section: Introductionmentioning
confidence: 99%